2009
DOI: 10.1007/s11033-009-9755-4
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane postconditioning protects isolated rat hearts against ischemia-reperfusion injury: the role of radical oxygen species, extracellular signal-related kinases 1/2 and mitochondrial permeability transition pore

Abstract: The roles of reactive oxygen species (ROS), extracellular signal-regulated kinase 1/2 (ERK 1/2) and mitochondrial permeability transition pore (mPTP) in sevoflurane postconditioning induced cardioprotection against ischemia-reperfusion injury in Langendorff rat hearts were investigated. When compared with the unprotected hearts subjected to 30 min of ischemia followed by 1 h of reperfusion, exposure of 3% sevoflurane during the first 15 min of reperfusion significantly improved functional recovery, decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…HPC appeared to modulate the endogenous ROS balance. The signaling role of ROS is also consistent with the significant blunting of the protective effects of postconditioning in isolated rat hearts and human myocardium by the ROS scavenger N-acetyl-L-cysteine or N-mercaptopropionylglycine [36, 37]. …”
Section: Discussionmentioning
confidence: 56%
“…HPC appeared to modulate the endogenous ROS balance. The signaling role of ROS is also consistent with the significant blunting of the protective effects of postconditioning in isolated rat hearts and human myocardium by the ROS scavenger N-acetyl-L-cysteine or N-mercaptopropionylglycine [36, 37]. …”
Section: Discussionmentioning
confidence: 56%
“…In the present study, we chose 3% sevoflurane to post-condition the isolated rat hearts in a Langendorff perfusion system [28] . Intracellular mitogenactivated protein kinases (MAPKs) signaling cascades play a key role in the pathogenesis of cardiac and vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane postconditioning has been reported to reduce myocardial infarct size and ameliorate cardiac functions in I/R rat hearts (Siegmund et al, 1997;Chen et al, 2008;Inamura et al, 2010). Some studies agreed that 3% sevoflurane postconditioning for 15 min conferred significant cardioprotection in isolated I/R rat hearts (He et al, 2008;Yao et al, 2010b), but our recent study found that 2.5% sevoflurane (1 MAC) postconditioning for 10 min was sufficient to improve myocardial function and reduce infarct size after global I/R in isolated rat hearts (Yu et al, 2010).…”
Section: Cardioprotection Effect Of Sevoflurane Postconditioningmentioning
confidence: 86%
“…A meta-analysis showed that sevoflurane reduces the rate of myocardial infarct size and mortality in patients undergoing cardiac surgery, though the underlying mechanism remains unclear (Landoni et al, 2007). Several recent studies have confirmed that sevoflurane postconditioning spares myocardial infarct size and improves contractile functions in I/R animals (Inamura et al, 2010;Yao et al, 2010b;Yu et al, 2010;Zheng et al, 2011). It is widely accepted that activating the phosphatidylinositol-3-kinase (PI3K)/Akt pathway is pivotal to cardioprotection by sevoflurane postconditioning against I/R injury (Yao et al, 2010a;Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation